Resource use and costs in high-risk symptomatic peripheral artery disease patients with diabetes and prior acute coronary syndrome: a retrospective analysis. Issue 2 (17th February 2016) - Reed Chase, Monica; Friedman, Howard S.; Navaratnam, Prakash; Heithoff, Kim; Simpson, Ross J.
ABSTRACT: Objectives : As the prevalence of peripheral artery disease (PAD) increases there is growing concern about the associated healthcare burden. This burden has not been well-characterized in high-risk patients with concurrent diabetes and/or acute coronary syndrome (ACS). The objective of this analysis was to assess comorbidities, medication use, outcomes, services and costs for 3 high-risk symptomatic PAD groups. Methods : This retrospective longitudinal analysis used the MarketScan Commercial Claims and Encounters Database (2005-2013). The 3 high-risk symptomatic PAD groups were (1) symptomatic PAD with/without diabetes, (2) symptomatic PAD with/without prior ACS, and (3) symptomatic PAD with/without diabetes and prior ACS. The study time frame was a period of 1-year before the earliest date of a symptomatic PAD record and 3 years post. Results : In all, 16, 663 symptomatic PAD patients were identified across the three risk groups. Mean age ranged from 66.4-67.4 years; the majority (55.0%-63.3%) were men. At 3 years post index, patients with symptomatic PAD and a risk factor had significantly higher use of beta-blockers, ACE inhibitors and statins ( P <0.0007), and higher rates of all-cause and symptomatic PAD-related medical services, diagnoses and procedures ( P <0.05). Clopidogrel and statins were used by ≤41.2% and ≤66.7% of symptomatic PAD patients without risk, respectively, and ≤68.9% and ≤80.2% of patients with risks. All cause and symptomatic PAD-related treatment costs ( P <0.0001) were higher for symptomatic PAD patients with risks versus patients without risks where annualized all-cause cost differences ranged from $7, 482 to $13, 504 and annualized PAD-related cost differences ranged from $605 to $1, 997. Conclusions : Symptomatic PAD patients with diabetes and/or prior ACS have significantly higher medical resource use and costs compared to symptomatic PAD patients without these risk factors. The utilization rate of secondary prevention therapies is suboptimal; therefore, greater effort must be made to increase utilization and optimize treatment to minimize the impact of symptomatic PAD.